Demystifying Scholarly Metrics : A Practical Guide - Vinyard, Marc W.; Colvin, Jaimie Beth (Bloomsbury Visual Arts, 2023)
Demystifying Scholarly Metrics gives librarians and faculty the confidence to navigate the maze of scholarly metrics, identify quality journals in which to publish, and measure the impact of scholarly works. Both librarians and professors can be overwhelmed by the bewildering number of scholarly metrics. This user-friendly book demystifies them, helping librarians become familiar with scholarly metrics and giving them the confidence to assist faculty at their institutions. It also equips faculty authors with the knowledge to evaluate journals and use metrics to track their scholarly impact. Several controversies exist in the scholarly metrics landscape, including a disagreement between the proponents of altmetrics and traditional bibliometrics. Even more contentious debates are breaking out over predatory journals and open access publishing. Authors Mark Vinyard and Jaimie Beth Colvin, who successfully launched a faculty publishing initiative, explain which aspects of metrics are truly essential to grasp, and they place these numbers in context. They help readers identify the metrics that are the best fit for their scholarship and give librarians and professors the tools to make smart decisions in this changing scholarly metrics landscape.
Keywords: Library science.; Library & information sciences